Evaluation and optimization of Plug and Abandon of well XX-01 on DELTA Field - Bima Putra Buana; Purnomosidi Purnomosidi; Akhmad Sofyan (Politeknik Energi dan Mineral Akamigas, 2021)
Plug and abandon operation may need to be applied on mature wells which have decreased oil and gas production less than others in economic benefits or exploration wells that may need to be side tracked with an option of new trajectory. This study evaluated and optimized cementing technique that being used on plug and abandon operation for well XX-01 which its location is on Delta Mahakam Field. The XX -01 well can’t be produced due to water breakthrough at its current producing layers, therefore, there will be a future sidetrack drilling as deepening project. Study results show that probability leakage rate is 5.76E-07 m3/s (0,000000576 m3/s) and according to ALARP triangle, the probability leakage rate of well XX-01 is on the acceptable risk zone therefore can be considered as a safe operation to be executed.